Introduction of principles of Green Economy into Russian industry - Sivkova A. I. (Topical issues of law, economic and management, 2022)
The article analyzes the concept of "Green Economy", examines the degree of implementation of the principles of "Green Economy" in the industrial sector of the Russian Federation and in the Russian economy
Keywords: зеленая экономика; промышленность РФ; экологические инвестиции; внедрение наилучших доступных технологий; Green Econony; Russian industry; environmental investment